# a community bike ride offers a short 5.7 mile ride for children and families. the short ride is followed by a long ride, 5 2/3 times as long as the short ride, for adults. if a woman bikes the short ride with her children, and then the long ride with friends. how many miles does she ride together?

38 miles

Further explanation

Given:

A community bike ride offers a short 5.7-mile ride for children and families.

The short ride is followed by a long ride, 5²/₃ times as long as the short ride, for adults.

A woman bikes the short ride with her children, and then the long ride with friends.

Question:

How many miles does she ride together?

The Process:

Let us make a pattern for the short ride:

Let us do a multiplication on a fraction at first.

We crossed out 3 and 57.

Then we make a pattern for the long ride, 5²/₃ (five and two third) times as long as the short ride:

A woman bikes the short ride with her children, and then the long ride with friends. Let's calculate how many miles does she ride together.

• The short ride:
• The long ride:

Thus, she rides 38 miles together.

1. What is the width of the actual snowflake? brainly.com/question/1070912
2. How much did Ciro spend altogether for the concert ticket, hotel, and dinner? brainly.com/question/12507869
3. How much more paint will Mathilde need to buy? brainly.com/question/36885

Keywords: A community bike ride, offers, a short 5.7-mile ride, for children and families, followed by, 5 2/3 times, for adults, a woman, with friends, how many miles, she ride together

Answer: First multiply 5.7 by 5 2/3 to figure out how long the adult ride is: 5.7/1 X 17/3= 32.3. Then add the adult ride and the children's ride together: 5.7+32.3=38 (7+3=10 which adds 1 to the whole number). The mom would ride 38 miles :)

## Related Questions

Use the substitution method to solve. 2x+y=20
-5y=-6x+12
( , )
please help, also give a step by step on how to solve this and ill mark brainliest

x = 7, y = 6

Step-by-step explanation:

solve for y for the first equation

2x + y = 20

-2x         -2x , eliminate 2x

y = 20-2x

now that we have found y, substitute the y in for the second equation

-5y = -6x + 12

-5(20-2x) = -6x + 12, we just changed y into 20-2x. remember that we are multiplying all of 20 - 2x by -5

-100+10x = -6x + 12, we multiplied everything from the parathesis  by -5

+100                 + 100, eliminate -100

10x = -6x + 112

+6x    +6x , eliminate 6x

16x = 112 , solve for x

x = 7

then y = 20 - 2x = 20 - 2*7 = 6

check:

2 * 7 + 6 = 20

20 = 20

-5 * 6 = -6 * 7 + 12

-30 = -42 + 12

-30 = -30

a map of a new dog park shows that it is triangular and that the sides measure 18.5m, 36.6 m, and 16.9 m. Are the dimensions correct?

First, you can draw a graph or coordinate plane to solve this. But i will do this for you.... OK, so the dimensions are correct, according to my graph... Don't worry, i did the coordinate plane for months in class... Your welcome and hope you do well for your hw.

Geometry question, please explain how you got to the answer so that i can do it myself on other questions as well, thanks!

AAS

Step-by-step explanation:

Here is the setting out proof with a - side note:

In Triangle JLM and Triangle JLK

Angle K is equal to Angle M (given) - This is a pair of matching angles

JK = JM (given) - This is a pair of matching sides

Since JL bisects KLM, Angle KLJ = Angle MLJ (Bisect means it cuts it in half, meaning the angle has been divided into two equal parts)  - This is a pair of matching angles.

Therefore, Triangle JLM and Triangle JLK are congruent (AAS) - The reason why we do AAS is because we have two pairs of matching angles and a pair of sides are equal. It is call AAS and not ASA, unknown reason but that is just how it is.

AAS

Step-by-step explanation:

< K = < L  (given)

<KLJ = < MLJ ( because  JL bisects < KLM)

JK = JM  (given)

we have 2 equal angles and one equal side with the 2 angles adjacent.

Help please its due tomorrow you'll get 25 points

1a) m^(3+6) = m^9

b) p^(8-2) = p^6

c) 2^4 n^(3*4) = 16n^12

2b) m^(6+7) = m^13

c) x^0 = 1
1a) m^9
1b) p^6
1c). 16n^12
2a). m^13
2b). 1

Yolanda owns 4 rabbits. She expects the number of rabbits to double every year.Write an equation to model this situation.

R=Number of rabbits

y=Years that have passed by { y ≥ 0 }

R=f(y) --> R is a function of y.
---------------------------------------------

Note that when:

y=0, R=4 ---> Point: (0, 4)

y=1, R=8 ---> Point (1, 8)

y=2, R=16 ---> Point (2, 16)

y=3, R=32 ---> Point (3, 32)

y=4, R=64 ---> Point (4, 64)

--------------------------------------------

So the equation you want is going to form a curved graph.

That equation is:

*You can test out this function on any decent graphing software.
This is an exponential function.

At year , the number of rabbits would be as follows:

Where x is the number of years

Which equation is identity? A.) 11-(2v+3)=-2v-8
B.) 5w+8-=6w-2 (w-4)
C.) 7m-2=8m+4-m
D.) 8y+9=8y-3